Misyjne nauczanie Jana Pawła II podczas pielgrzymek do Polski - Adamiak, Grzegorz (Annales Missiologici Posnanienses, 2020)
During his pilgrimages to his homeland, John Paul II was teaching his countrymen about the problems specifi c to the Church in Poland, but also to the whole Church. One of these themes was the missions ad gentes. The Pope noticed and pointed out on the example of the history of his nation that missions built Polish statehood and shaped Polish culture. He called for this process to be recognized in the history of Europe as a whole and to recognize in evangelization the factor that builds and defi nes its true identity. He showed that missions help imbue human culture with a supernatural element. He recalled the truth about the missionary nature of the Church and the missionary vocation of all its members. Responsibility and cooperation in the missionary work was for John Paul II one of the forms of the “imagination of mercy.” Appealing to his countrymen for missionary generosity and commitment, he also pointed to the fi gures who were involved in the animation of the missionary work in the Polish and universal Church. In his teaching in Poland, he recalled the missionary task of the Church community and of each and every faithful.